Western and Secular Concept of Socialism as Depicted in the Animal Farm by George Orwell: Western and Secular Concept of Socialism as Depicted in the Animal Farm by George Orwell (Khairulummah, 2022)
AbstractAnimal Farm is a well-known satirical allegorical novella by George Orwell. It depicts the story of a group of farm animals who rebel against their human farmer named Mr. Jones. The farm animals want to make a society where they can be equal, free of charge, and blissful. At the end, the rebellion is betrayed, and the farm ends up in a state as worst as it was before, under the dictatorship of a pig named Napoleon. Socialism is found in the beginning of the story when the revolution takes place in the farm. The most noteworthy commandment is that all animals are equal which is based on socialism and the way the farm is run after revolution is clear signal of socialism. According to Orwell, the fable reflects events which lead to the Russian Revolution of 1917 and then into the Stalinist era of the Soviet Union. Orwell was a democratic socialist and he was a critic of Joseph Stalin and antagonistic towards Moscow-directed Stalinism. Therefore, it is a bitter critique of the rhetoric of the Russian Revolution and the story of the emergence and development of Soviet Communism is described in the form of an animal allegory and it allegorizes ascend to power of the dictator named Joseph Stalin.
Keywords: satirical allegorical novella, George Orwell, Joseph Stalin, Stalinism, Napoleon